The Endocrine Disrupting Chemical Tolylfluanid Alters Adipocyte Metabolism via Glucocorticoid Receptor Activation - Neel, Brian A. (Endocrine Society, 2013)
Glucocorticoid signaling plays a critical role in regulating energy metabolism. Emerging data implicate environmental endocrine-disrupting chemicals as contributors to the obesity and diabetes epidemics. Previous studies have shown that the phenylsulfamide fungicide tolylfluanid (TF) augments glucocorticoid receptor (GR)-dependent luciferase expression in 3T3-L1 preadipocytes while modulating insulin action in primary murine and human adipocytes. Studies were performed to interrogate glucocorticoid signaling in primary adipocytes exposed to TF. TF mimicked the gene transcription profile of the murine glucocorticoid corticosterone (Cort). Cellular fractionation assays demonstrated that TF treatment promoted the activating serine phosphorylation of GR, augmenting its cytoplasmic-to-nuclear translocation as well as its enrichment at glucocorticoid response elements on the glucocorticoid-induced leucine zipper gene promoter. After acute treatment, Cort or TF promoted insulin receptor substrate-1 (IRS-1) gene and protein expression. Either treatment also enriched GR binding at an identified glucocorticoid response element in the IRS-1 gene. TF or Cort each increased insulin-stimulated lipogenesis, an effect resulting from increased lipogenic gene expression and enhanced insulin-stimulated dephosphorylation of acetyl-coenzyme A carboxylase. The augmentation of insulin-stimulated lipogenesis was mediated through a specific enhancement of Akt phosphorylation at T308. These findings support modulation of IRS-1 levels as a mechanism for glucocorticoid-mediated changes in insulin action in primary adipocytes. Albeit with less affinity than Cort, in silico analysis suggests that TF can interact with the ligand binding pocket of GR. Collectively, these studies identify TF as a structurally unique environmental glucocorticoid. Glucocorticoid signaling may thus represent a novel pathway by which environmental toxicants promote the development of metabolic diseases.